AN ANALYSIS OF ENGLISH TEACHING STRATEGIES THROUGH ONLINE CLASSES DURING PANDEMIC COVID-19 - Nanning; Jumrah; Dirgayanti Fernandez (Inspiring: English Education Journal, 2022)
Teaching strategy is a plan, method or series of activities designed for the following purposes achieve certain learning goals. teaching strategy designed to achieve specific goals. Which means from making a strategy is to achieve a goal. In this study the researcher want to see how the teacher's strategy in implementing the learning process, especially in managing the online class at UPT SMA Negeri 4 Parepare. This research focused on the teachers’ strategies used in teaching English through online classes during the COVID-19 Pandemic. This study aimed at answering the following research questions (1) What are the obstacle of strategies in English teaching through online classes during COVID-19 pandemic at UPT SMA Negeri 4 Parepare? (2) How is the effectiveness of teachers’ teaching strategy of teaching English during COVID-19 pandemic at UPT SMA Negeri 4 Parepare? This type of research was field research with qualitative approach. Data collection techniques in this research are In-depth interview, observation checklis and documentation. The result of study showed that (1) Monitor the student , Student Motivation (2) The strategy of English teachers in teaching English in online classes has not been said to be effective because they only provide understanding of the material, after that give assignments.